2019
DOI: 10.5005/jp-journals-10071-23123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Segmental Thoracic Epidural Block on Pancreatitis Induced Organ Dysfunction: A Preliminary Study

Abstract: Background This preliminary randomized controlled study evaluated effect of thoracic epidural block (TEB) on progression of acute pancreatitis induced organ dysfunction/failure. Materials and Methods Patients with predicted severe acute pancreatitis, without contraindication to TEB were randomized to receive (group TE) or not receive a TEB (group NTE) (n = 16 each). For group TE, TEB was performed at T8-9 or T9-10 vertebral level, with infusion of ropivacaine (0.2%) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Thoracic epidural analgesia was associated with improvement of serum procalcitonin, 4 lower incidences of acute mesenteric ischemia, 10 and lower incidences of acute kidney injury 10 . However, TEA had no impact on locoregional complications or septic complications 3,10 .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Thoracic epidural analgesia was associated with improvement of serum procalcitonin, 4 lower incidences of acute mesenteric ischemia, 10 and lower incidences of acute kidney injury 10 . However, TEA had no impact on locoregional complications or septic complications 3,10 .…”
Section: Resultsmentioning
confidence: 95%
“…The 2 clinical trials both showed high risk of bias, particularly in outcome measurement 3,4 . Among the nonrandomized studies, 1 had moderate risk of bias, 10 whereas 5 had high risk of bias.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations